Physio Kundalini syndrome and mental health - Valanciute, A. (Mental health, religion & culture, 2011)
The increasing practice of traditional eastern philosophies within the modern society has highlighted the difficulties of assimilation of these traditions within Western culture. This invariably results in difficulties on the part of the practitioners to integrate these practices into their daily lifestyle. The reasons for these are often complex. One of the contributing factors could be insufficient understanding or acquisition of a superficial interpretation of the eastern tradition or philosophies. The Kundalini concept comes from the yogic philosophy of ancient India and refers to mothering intelligence behind yogic awakening and spiritual maturation. We describe a case of a young male who presented with functional deterioration experiencing psychotic symptoms, which he describes as his Kundalini awakening.